2015
DOI: 10.3168/jds.2014-9183
|View full text |Cite
|
Sign up to set email alerts
|

Glucose supplementation has minimal effects on blood neutrophil function and gene expression in vitro

Abstract: During early lactation, glucose availability is low and the effect of glucose supply on bovine polymorphonuclear leukocyte (PMNL) function is poorly understood. The objective of this study was to determine the effect of glucose supplementation on the function and transcriptomic inflammatory response of PMNL from cows in early and mid-lactation in vitro. Twenty Holstein cows in early (n=10; days in milk=17±3.1) and mid-lactation (n=10; days in milk=168±14.8) were used for this study. Jugular blood was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…A lack of stage of lactation effect was also observed in the expression of genes coding for inflammatory PMN receptors, signaling factors, cytokines, enzymes, and receptors involved in glucose and AA metabolism (for a complete list of genes and their effects see Supplemental Table S4; http://dx.doi.org/10.3168/jds.2015-10086). In a recent paper (Garcia et al, 2015b) we also observed that stage of lactation did not alter PMN function and minimal differences in gene expression were observed after glucose supplementation.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…A lack of stage of lactation effect was also observed in the expression of genes coding for inflammatory PMN receptors, signaling factors, cytokines, enzymes, and receptors involved in glucose and AA metabolism (for a complete list of genes and their effects see Supplemental Table S4; http://dx.doi.org/10.3168/jds.2015-10086). In a recent paper (Garcia et al, 2015b) we also observed that stage of lactation did not alter PMN function and minimal differences in gene expression were observed after glucose supplementation.…”
supporting
confidence: 53%
“…Thirteen primiparous and 5 multiparous (≥2 lactations) Holstein cows in early (n = 9; DIM = 17 ± 3.2; 34.0 kg of milk/d) and mid lactation (n = 9; DIM = 165 ± 14.4; 38.6 kg of milk/d) were used for this study. Details regarding animal selection, housing, management, isolation of PMN, and analysis are described in Garcia et al (2015b). Jugular blood (~150 mL) was collected from cows in early and mid lactation.…”
mentioning
confidence: 99%
See 3 more Smart Citations